Relationship between harvest time and the presence of insects pests in stored corn - SUÁREZ-GÓMEZ, HERNANDO (Revista Colombiana de Entomología, 1994)
This study was carried out at the Research Center «Motilonia» of ICA, in Codazzi (Cesar). Environmental conditions were: temperature 28°C, 68% of relative humidity, and 1.294 mm of rainfall. Observations were conducted during three years, in order to establish the relationship between different harvest times, storage methods, and the presence of insects in the grain. The corn varieties used were ¡CA V-106, ICA V-155, Precocious Yellow, and White Urumita or Native. In the field, random samples were taken from each genotype one month after flowering up to the moment the grain moisture was around 15%. The samples were taken to the laboratory and preserved in glass jars. Corn ears with husks, corn ears alone, husks, corn husks, and grains were stored separately. Five insects species were identified, being the most important because if its abundance, Cathartus quadricollis (Guérin-Méneville) (Coleoptera: Cucujidae) and Sathrobrota rileyi (Walsingham) (Lepidoptera: Cosmopterygidae). The lowest insect populations were found when the grains were stored alone. However, variations of the number of insects were found within semesters in relation to the harvest time and the storage method.